Acoustic Microfluidics - Zhang, Peiran (Annu Rev Anal Chem (Palo Alto Calif), 2020)
Acoustic microfluidic devices are powerful tools that use sound waves to manipulate micro- or nanoscale objects or fluids in analytical chemistry and biomedicine. Their simple device designs, biocompatible and contactless operation, and label-free nature are all characteristics that make acoustic microfluidic devices ideal platforms for fundamental research, diagnostics, and therapeutics. Herein, we summarize the physical principles underlying acoustic microfluidics and review their applications, with particular emphasis on the manipulation of macromolecules,cells,particles,model organisms, and fluidic flows.We also present future goals of this technology in analytical chemistry and biomedical research, as well as challenges and opportunities.